Long-Run Changes in the Concentration of Wealth: An Overview of Recent Findings - Daniel Waldenström; Henry Ohlsson; Jesper Roine (Research Institute of Industrial Economics (IFN), 2007)
The objective of this paper is to study the dynamics of the wealth distribution over the path of economic development. More specifically, we are interested in distinguishing between changes which seem to be country specific and characteristics shared by all countries. A historical account of the evolution of the wealth distribution in developed countries is interesting in itself, but it can also hold implications for countries that are currently in an early stage of development or in transition. The data used originates from the taxation of wealth and estates.
Keywords: D31; H20; J30; N30; 330; Wealth Concentration; Inequality; Income Distribution; Wealth Distribution; Sweden; Vermögensverteilung; Einkommensverteilung; Entwicklung; Westliche Staaten